Reproductive parameters of male rats treated with Pavetta crassipes K.Schum. aqueous leaf extract - Moses W. Bariweni; Oboma I. Yibala; Tolulokpe O. Alade; Doubra F. Karibo (GarVal Editorial Ltda., 2019)
Context: There is a growing concern about induction of male infertility resulting from medicinal plant use especially in malaria treatment. Carica papaya and Azadirachta indica are plants with documented antimalarial and anti-fertility effects. Pavetta crassipes leaves are reported to have antimalarial effects but there is no information about its reproductive toxicology. Aim: To evaluate the effects of P. crassipes aqueous leaf extract on male reproductive parameters. Methods: Healthy adult male rats were used for this study. The extract was administered orally at 400, 800 and 1600 mg/kg for two and four weeks, respectively while the control group received 10 mL/kg distilled water. Blood samples were collected for serum hormonal assay. The testes and epididymis were excised for histological examination and seminal fluid analysis. Results: Serum testosterone, follicle stimulating hormone (FSH) and luteinizing hormone (LH) levels reduced significantly in all treated groups compared to control but this effect was reversed after the respective recovery periods except FSH and LH levels in the group treated with 1600 mg/kg for four weeks. The control group had normal testicular histology while varying degrees of reversible histological changes occurred in the treated groups except persistent irregular basal lamina at 800 mg/kg in the two-week treated group while persistent irregular basal lamina and tubular atrophy occurred at 1600 mg/kg in the four-week treated group. Sperm count reduction at 800 and 1600 mg/kg compared to control (86 x 106 mL-1) in the groups treated for four weeks was irreversible. Conclusions: The aqueous leaf extract of Pavetta crassipes has the potential to cause deleterious effects on male reproductive function in Wistar rats.